Three prevalent mutations in a patient with phenylalanine hydroxylase deficiency: implications for diagnosis and genetic counselling. Issue 2 (February 1996) - Guldberg, P; Levy, H L; Henriksen, K F; Guttler, F
Abstract : Mutation analysis in a patient with mild hyperphenylalaninaemia showed three distinct base substitutions in exon 12 of the phenylalanine hydroxylase (PAH) gene. All three mutations, R413P, Y414C, and D415N, have previously been described as being independently associated with PAH deficiency. Family studies and independent analysis of the PAH alleles of the patient showed cosegregation of the R413P and Y414C mutations. Data on the ethnic background of the family provide evidence that the R413P mutation has occurred on a PAH allele carrying the Y414C mutation. Using current methods for mutation identification, the presence of two known mutations on a single PAH allele implies the risk of misdiagnosis of PAH deficiency and complicates genetic counselling. Our results stress the need for comprehensive mutation scanning of the PAH gene in diagnostic settings.